The theory and practice of regional strategy: a response to Osegowitsch and Sammartino - Rugman, Alan M; Verbeke, Alain (Journal of International Business Studies, 2008)
We are grateful to Osegowitsch and Sammartino for their critical analysis of our work on the regional and global strategies of multinational enterprises (MNEs). In this response, we demonstrate that changing the quantitative thresholds for classifying MNEs as global vs non-global has no bearing on our earlier conclusions. First, very few global firms exist. Second, scholarly reflection on regional vs global MNE strategy requires substantive extensions of extant international business theory.